eESH an extensible expert system for health - Agustin, Grace Anne
A clinical decision support system (CDSS) is a medical system designed to simulate the presence of an expert in a specific field of health. This is useful in aiding medical decisions when there is no expert present. Here we have a system designed to be able to accept information and be used for different fields of health. The CDSS is composed of two major elements: the knowlegde base, which contains pertinent information to the field of health that is currently being used, and the inference engine. Signs and symptoms are accepted as input, by this system, and an output of the corresponding cause, dictated by the particular field that the system currently uses. A knowledge acquisition tool (KAT) has also been implemented to allow experts to dynamically update the knowledge base, together with a browser for the knowledge base itself as well. This paper describes the structure of the fully-developed system, from the design and interface of the CDSS to the implementation of the System as a web service. CLIPS (C Language Integrated Production System) is also discussed, specifically, its inference mechanism. The system is applied to both Poisoning and Infection for testing. Keywords Expert System, Clinical Decision Support System, Medical Tool, Inference Engine.